Recombinant human hair keratin proteins for halting bleeding. (5th November 2018) - Guo, Tingwang; Li, Wenfeng; Wang, Ju; Luo, Tiantian; Lou, Deshuai; Wang, Bochu; Hao, Shilei
Abstract: Keratins derived from human hair have been widely used for tissue engineering. However, some drawbacks relative to the traditional keratins extracts have been found: (a): difficultly controlling the amino acid composition; (b): batch to batch inconsistent quality; and (c): producing complex keratin and keratin-associated proteins (KAPs), which problems have made some studies concerning human hair keratins stagnant, especially in the mechanism studies related to hemostasis of keratins. Herein, a type-I human hair keratin of K37 and a type-II human hair keratin of K81 were heterologously expressed and firstly used for haemostatic application. SDS-PAGE analysis shows that the recombinant keratins had higher purity compared to the extracted keratins. The circular dichroism (CD) spectra of K37 and K81 suggested that the secondary structures were rich in α-helix. In addition, the recombinant keratin proteins could enhance fibrin colt formation at the site of injury and decrease the bleeding time and blood loss in liver puncture and femoral artery injury rat models. This study provides a new strategy for future works involving design and mechanism studies of keratin biomaterials. Graphical Abstract: